Perancangan Aplikasi Pembelajaran Berbasis Multimedia Pada Anak Usia Dini (PAUD) - Widiantoro, Angga Tegar; , Husni Thamrin S.T., M.T., Ph.D (2016)
PAUD is represent most elementary education ladder. Elementary education for child with age one till six years. Many teacher and parent that start important realizing to give elementary education on this period. Many people mentioning it with a period of gold (golden age). Most teacher or instructor only submitting lesson by oral and do duty. Without developing before context of learn in this case cognate aspect get very big stimuli, while the other aspect is almost disregarded. Giving of items learn in PAUD tend to more focused by activity of academy and tend to drag on because of often disregard aspect play at. At this research, research will design a study application being based on multimedia. To design this application is required by some conducted survey in some PAUD, which later will be made as guidance to design this application. Result of from research, a application that able to assist the instructor in giving of items learn to student. Where this application can improve student enthusiasm in learning and tend to do not drag on.